Three new species of Pleurothallis (Orchidaceae) from Costa Rica and Panama, with a note on asexual reproduction by prolification in Pleurothallidinae - Adam P. Karremans; Franco Pupulin; John Gange; Diego Bogarín (PhytoKeys)
Three new species of Pleurothallis, each exhibiting prolific vegetative growth, are described from Costa Rica and western Panama. Prolification refers to the development of a vegetative bud from the axil of a bract within the floral meristem, a frequent condition in the Pleurothallidinae, where it manifests as a new ramicaul developed from the apex of a previous ramicaul. Prolification can be either constitutive or facultative, the latter occurring mostly under stress-induced, non-optimal growing conditions. The three new species are found at high elevations, between 1400 and 2550 m, in humid, dense, mossy conditions on the Talamanca range, where they naturally produce prolific growths on the ramicaul apex that sever from the plant with time. Pleurothallis matrisilvae sp. nov. superficially resembles P. bothros, but may be distinguished by the prolific habit, thin ramicauls, typically bearing 1–2 open flowers, the longer flower segments, the lanceolate petals, and the black flecks on the pedicel, ovary, and external surface of the sepals. Pleurothallis pridgeoniana sp. nov. is similar to P. vinealis but distinguished by the significantly shorter plants and ramicauls, the much smaller yellow flowers with a rose to purple suffusion, and the triangular-ovate lip with glandular margins and lacking a central sulcus. Pleurothallis winkeliana sp. nov., closely resembles P. longipetala, but differs by the occasionally prolific plant that produces clumps of ramicauls, the comparatively broader, cordate leaves with overlapping basal lobes, the smaller flower, and the pendent lip, perpendicular to the column.